2020
DOI: 10.1016/j.abb.2020.108364
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical characteristics of the brown seaweed carotenoid fucoxanthin

Abstract: Fucoxanthin (Fx), a major carotenoid found in brown seaweed, is known to show a unique and wide variety of biological activities. Upon absorption, Fx is metabolized to fucoxanthinol and amarouciaxanthin, and these metabolites mainly accumulate in visceral white adipose tissue (WAT). As seen in other carotenoids, Fx can quench singlet oxygen and scavenge a wide range of free radicals. The antioxidant activity is related to the neuroprotective, photoprotective, and hepatoprotective effects of Fx. Fx is also repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 192 publications
(270 reference statements)
1
41
0
1
Order By: Relevance
“…It has a distinctive structure with an allenic bond, a 5, 6-monoepoxide, and nine conjugated double bonds. Fucoxanthin is known to show a unique and wide variety of biological activities, therefore, good sources of this marine carotenoid have been explored 31 . Although fucoxanthin can be synthesized chemically, extraction from brown seaweeds and microalgae is a more accessible, safe, and economic method 42 .…”
Section: Total Lipids and Fucoxanthin Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a distinctive structure with an allenic bond, a 5, 6-monoepoxide, and nine conjugated double bonds. Fucoxanthin is known to show a unique and wide variety of biological activities, therefore, good sources of this marine carotenoid have been explored 31 . Although fucoxanthin can be synthesized chemically, extraction from brown seaweeds and microalgae is a more accessible, safe, and economic method 42 .…”
Section: Total Lipids and Fucoxanthin Contentsmentioning
confidence: 99%
“…They include the most well-known β-carotene and lutein found in terrestrial plants together with a variety of specific carotenoids to only found in algae, cyanobacteria, and several species of yeast 30 . Among these carotenoids, fucoxanthin is known to reduce the risk of a surprisingly wide variety of dysfunctions and diseases, including metabolic syndrome, obesity, heart disease, diabetes, cancer, hypertension, as well as reactive oxygen species-and inflammation-associated disorders 31 . Brown seaweeds are possible source of fucoxanthin, but the content is not high ranging up-to 0.7 mg g 1 dry weight 32 .…”
Section: Introductionmentioning
confidence: 99%
“…They investigated the polymorphism status of uncoupling protein 1 (UCP1) in the subjects [ 33 ]. UCP1, a mitochondrial membrane protein, plays a central role in the metabolic thermogenesis process for inhibiting excessive fat accumulation [ 167 ]. The UCP1 molecule is strongly expressed in brown adipose tissue (BAT), which promotes whole body energy expenditure, and its protein aberration leads to the development of obesity, although most fat is accumulated in the white adipose tissue (WAT), where UCP1 is absent.…”
Section: Beneficial Effects Of Brown Algae and Fx In Humanmentioning
confidence: 99%
“…Fucoxanthin is a xanthophyll exhibiting several health benefits. This compound has remarkable biological properties for human health [109], such as anti-inflammatory activity [108][109][110][111][112][113][114][115], hepatoprotective effect [12,98,[116][117][118], cardioprotective activity [119][120][121], anticancer [26,116,119,[122][123][124][125][126][127][128][129][130][131], antidiabetic [75,[132][133][134], antiobesity [135][136][137][138][139], antioxidant [65,131,[140][141][142][143][144][145][146], skin protective effect…”
Section: Fucoxanthin and Their Biological Activitiesmentioning
confidence: 99%